THE STATE, CONTRADICTIONS AND TRENDS OF DEVELOPMENT OF THE INFORMATION FIELD OF TECHNOLOGICAL PROCESSES AT THE AIRPORT - Тамаргазін, О. А.; Ліннік, І. І.; Курбет, Л. В. (Science-based technologies, 2017)
In this article, we conducted analysis of the current state of the information field and its components to ensure the technological processes at airports. We examined the organizational-legal, engineering, and technological elements in the information field the airport. We analysed the situation and identified shortcomings in the provision of structural subdivisions of the airports modern information technology. We have identified contradictions in the development of the information field at the airport that allowed us to identify and find solutions to help make qualitatively new properties of information technology with the goal of ensuring airport staff are consistent and complete information to make informed and timely decisions in any real industrial situation.